Antibacterial kaneoheoic acids A-F from a Hawaiian fungus Fusarium sp. FM701. (January 2021) - Uz Zaman, KH Ahammad; Wu, Xiaohua; Hu, Zhenquan; Yoshida, Wesley; Hou, Shaobin; Saito, Jennifer; Avad, Kristiana Alexes; Hevener, Kirk E.; Alumasa, John N.; Cao, Shugeng
Abstract: Alarming rate of resistance to the existing antibiotics exhibits the importance of developing new antibiotic molecules from relatively under explored sources as well as implementing alternative approaches like antibiotic adjuvants. Six previously undescribed fungal polyketides, kaneoheoic acids A-F (1 –6 ) were isolated from a fungal strain Fusarium sp . FM701 which was collected from a muddy sample of Hawaiian beach. The structures of these six compounds were elucidated by spectroscopic interpretation, including HRESIMS and NMR, and electronic circular dichroism (ECD) analysis. All six compounds that were inactive when tested alone showed significant antibacterial activity against Staphylococcus aureus and Bacillus subtilis, in the range of 10–80 μg/mL when assayed in combination with either chloramphenicol (half of the MIC, 1 μg/mL), an FDA approved antibiotic or disulfiram (6 μg/mL), an established antibiotic adjuvant that augmented the activity of antibiotics. Graphical abstract: Image 1 Highlights: Kaneoheoic acids A-F (1–6) are previously undescribed fungal polyketides. The absolute configuration of compounds 2–4 was determined. All six compounds showed significant antibacterial activity in combination assay. None of compounds 1–6 showed cytotoxicity at 40 μg/mL.